A taxonomic revision of the genus Paradynomene Sakai, 1963 (Crustacea: Decapoda: Brachyura: Dynomenidae) - Mclay, Colin L.; Ng, Peter K.l. (Zootaxa, 2004)
The Indo West Pacific dynomenid genus Paradynomene Sakai, 1963, previously regarded as monotypic, is revised and six species are now recognized, viz. P. tuberculata Sakai, 1963, P. quasimodo n. sp., P. demon n. sp., P. diablo n. sp., P. teufel n. sp. and P. rotunda n. sp.. Most of the species are from deep to relatively deep waters with only one species (P. rotunda) known from shallow water. The species are distinguished by a combination of carapace features, notably carapace shape and height, form of the areolae, and position of major tubercles.